Implementation of Solar-PV Inverter as STATCOM during Nighttime in Grid-Connected System (PV-STATCOM) - Tamrakar, Indraman; Joshi, Kishor; Karki, Pranisha; Bimali, Sagar; Aryal, Tara (Journal of the Institute of Engineering, 2020)
Grid-connected PV-system generates active power only during daytime and it remains completely idle or sleeping during nighttime. In an interconnected power system balance between active and reactive power consumption and generation is very essential to maintain the frequency and voltage constant. The current trend is that the reactive Power is either supplied by generators or by separate reactive Power compensators such and shunt capacitor, STATCOM, etc. If the grid needs reactive power during night time, the sleeping inverter of the solar-PV system can be used as a reactive power generator without exceeding the volt-amp rating of the inverter and this scheme is named PV-STATCOM in this paper. This paper presents the concept of PV-STATCOM and its control logic. The inverter of the grid-connected Solar-PV system acts as an active power generator during daytime and reactive power generator during nighttime. The proposed scheme is simulated in MATLAB Simulink and the simulation results are presented. The simulation result shows that the proposed control logic for PV- STATCOM works satisfactorily.